Porous Al-Ce-based composite material as well as preparation method and application thereof

By using porous Al-Ce-based composite materials as adsorbents, using their porous structure and hydrolysis to form hydroxyl groups, the problem of poor effect of removing fluorine and arsenic ions in geothermal water in the prior art is solved, and the effect of efficient removal of fluorine and arsenic ions is achieved, meeting the limit standards of surface water.

CN119819249APending Publication Date: 2025-04-15TIBET UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411878906.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing oxide adsorbents have poor results when removing high concentrations of fluorine and arsenic ions in geothermal water, and the residual fluorine concentration after adsorption does not meet the limit standards of surface water.

Method used

A porous Al-Ce-based composite material is used as the adsorbent, including aluminum cerium oxide and aluminum cerium sulfate, and is prepared in an oxygen-containing atmosphere by calcining a mixture of soluble cerium salt and aluminum salt to form a composite material with a porous structure. The material is able to hydrolyze to form hydroxyl groups and effectively remove fluorine and arsenic ions through ion exchange and adsorption.

Benefits of technology

The adsorption rate of fluoride ions in geothermal water reached 91.47%, the adsorption rate of arsenic ions reached 93.8%, and the residual concentration of fluorine and arsenic ions after adsorption meets the limit standards of surface water.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819249A_ABST
    Figure CN119819249A_ABST
Patent Text Reader

Abstract

The invention provides a porous Al-Ce-based composite material as well as a preparation method and application thereof, and belongs to the technical field of adsorption materials. The porous Al-Ce-based composite material is composed of aluminum cerium oxide and aluminum cerium sulfate. The aluminum cerium oxide comprises aluminum oxide and cerium oxide; the aluminum cerium sulfate comprises CeOSO4 and Al2 (SO4) 3; the BJH pore size distribution average value of the porous Al-Ce based composite material is 24.01 nm to 30.18 nm. When the porous Al-Ce-based composite material provided by the invention is used as an adsorbent for water treatment, the porous Al-Ce-based composite material can be hydrolyzed to form hydroxyl groups, and the hydroxyl groups, fluorine ions and arsenic ions are subjected to ion exchange and adsorption, so that the fluorine ions and the arsenic ions in water are effectively removed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adsorption materials, and in particular relates to a porous Al-Ce based composite material and a preparation method and application thereof. Background Art

[0002] Geothermal water is a cheap, clean, abundant new energy source and precious water resource. However, geothermal water often contains high concentrations of harmful substances such as fluorine and arsenic. The total arsenic concentration in the water body is as high as 5.7 mg / L, and the fluoride ion concentration is as high as 18 mg / L, which is far higher than the limit of fluorine and arsenic in the surface water environmental quality standard (GB2828-2002). Directly discharging geothermal water tail water into the receiving water body will not only affect the ecological environment of the basin, but also have adverse effects on organisms and humans. Therefore, it is urgent to solve the problem of fluorine and arsenic removal from geothermal water. The treatment of geothermal water to achieve safe discharge is of great significance to the protection of the ecological environment.

[0003] At present, the removal of fluoride and arsenic ions in geothermal water mainly adopts the adsorption method of adsorbents. Common adsorbents are oxide adsorbents, mainly MgO, Fe2O3, Al2O3, TiO2 and CeO2. However, the adsorption effect of these oxide adsorbents is not good. Taking commercial CeO2 as an example, when the solid-liquid ratio of fluoride ion solution and commercial CeO2 is 1g / L, its adsorption efficiency for fluoride is only 11.54%. The residual fluoride concentration after adsorption still does not meet the limit standard of fluoride in surface water. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a porous Al-Ce based composite material and a preparation method and application thereof. The porous Al-Ce based composite material provided by the present invention can be used as an adsorbent to effectively remove fluoride ions (F - ) and arsenic ions (mainly HAsO4 2- The residual concentrations of fluoride and arsenic ions after adsorption meet the limit standards for fluoride and arsenic in surface water.

[0005] In order to achieve the above object, the present invention provides the following scheme:

[0006] The present invention provides a porous Al-Ce based composite material, comprising aluminum-cerium oxide and aluminum-cerium sulfate; the aluminum-cerium oxide comprises aluminum oxide and cerium oxide; the aluminum-cerium sulfate comprises CeOSO4 and Al2(SO4)3; the BJH pore size distribution average value of the porous Al-Ce based composite material is 24.01-30.18 nm.

[0007] Preferably, the specific surface area of ​​the porous Al-Ce-based composite material is 2.45 to 22.41 m 2 / g, pore volume is 0.001~0.052cm 3 / g, particle size is 200nm.

[0008] The present invention provides a method for preparing the porous Al-Ce based composite material described in the above scheme, comprising the following steps:

[0009] A mixture of a soluble cerium salt and a soluble aluminum salt is calcined in an oxygen-containing atmosphere to obtain the porous Al-Ce-based composite material; the soluble cerium salt includes Ce(SO4)2·4H2O and / or Ce(SO4)2·2(NH4)SO4; the soluble aluminum salt includes Al2(SO4)3·18H2O.

[0010] Preferably, the calcination temperature is 400-700° C. and the calcination time is 1-5 hours.

[0011] Preferably, the mass ratio of aluminum in the soluble aluminum salt to cerium in the soluble cerium salt is (0-10):(0-10), and both are not 0.

[0012] Preferably, the calcination atmosphere is air.

[0013] Preferably, the preparation of the mixture of the soluble cerium salt and the soluble aluminum salt comprises: mixing the soluble cerium salt, the soluble aluminum salt and water, and heating to evaporate the water to obtain the mixture of the soluble cerium salt and the soluble aluminum salt.

[0014] Preferably, the heating temperature is 60-90°C.

[0015] The present invention provides the use of the porous Al-Ce-based composite material described in the above scheme or the porous Al-Ce-based composite material prepared by the preparation method described in the above scheme as an adsorbent in water treatment.

[0016] Preferably, the concentration of the porous Al-Ce-based composite material in the water to be treated is 0.2-1 g / L; the fluoride ion concentration in the water to be treated is ≤17.55 mg / L, and the arsenic ion concentration is ≤2.39 mg / L.

[0017] The present invention provides a porous Al-Ce-based composite material, including aluminum cerium oxide and aluminum cerium sulfate; the aluminum cerium oxide includes aluminum oxide and cerium oxide; the aluminum cerium sulfate includes CeOSO4 and Al2(SO4)3; the average BJH pore size distribution of the porous Al-Ce-based composite material is 24.01-30.18nm. The porous Al-Ce-based composite material provided by the present invention can be hydrolyzed to form hydroxyl groups when used as an adsorbent for water treatment, and ion exchange and adsorption with fluoride ions and arsenic ions can be carried out, thereby effectively removing fluoride ions (F - ) and arsenic ions (mainly HAsO4 2-exist).

[0018] In addition, since the Al-Ce composite material provided by the present invention has a porous structure, the exposure of the bifunctional groups (i.e., hydroxyl and sulfate groups, which are not completely converted into cerium oxide and aluminum oxide after calcination, and sulfate groups still remain in the composite) is increased, thereby increasing the active adsorption sites of the adsorbent, which is conducive to the contact between the target pollutants in the aqueous solution and the adsorbent, thereby achieving the removal of fluorine and arsenic ions in the water. The results of the embodiment show that the adsorption rate of the porous Al-Ce-based composite material provided by the present invention for fluorine ions is 91.47%, the adsorption rate for arsenic ions is 93.8%, and the adsorption capacity for fluorine ions and arsenic ions is 297 mg / g and 251 mg / g, respectively.

[0019] The present invention provides a method for preparing the porous Al-Ce-based composite material described in the above scheme, comprising the following steps: calcining a mixture of a soluble cerium salt and a soluble aluminum salt to obtain the porous Al-Ce-based composite material; the soluble cerium salt includes Ce(SO4)2·4H2O and / or Ce(SO4)2·2(NH4)SO4; the soluble aluminum salt includes Al2(SO4)3·18H2O. In the present invention, a part of the sulfate radical generates water, sulfur dioxide and oxygen during the calcination process. Due to the loss of these gases, pores are formed, which act as a pore-forming agent, thereby forming a porous Al-Ce-based composite material, and the other part is retained in the composite material. This porous Al-Ce-based composite material can be hydrolyzed to form hydroxyl groups when used as an adsorbent for water treatment. The sulfate radicals retained in the composite material and the hydroxyl groups formed by hydrolysis are ion exchanged and adsorbed with fluoride ions and arsenic ions, thereby effectively removing fluoride ions and arsenic ions in water. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0021] Figure 1 The present invention is a schematic diagram of the preparation of the adsorbent porous Al-Ce-based composite material and the process of removing fluorine and arsenic from geothermal water;

[0022] Figure 2 The figure is the effect of the porous Al-Ce based composite materials obtained with different Al / Ce mass ratios in Examples 1 to 9 and Comparative Examples 1 to 2 on the arsenic adsorption effect;

[0023] Figure 3The figure is the effect of the porous Al-Ce based composite materials obtained with different Al / Ce mass ratios in Examples 1 to 9 and Comparative Examples 1 to 2 on the fluorine adsorption effect;

[0024] Figure 4 The effects of different calcination temperatures on the adsorption of fluoride ions in Examples 10 to 17 and Comparative Examples 3 to 10 are shown;

[0025] Figure 5 This is a transmission electron microscope micrograph of the porous Al-Ce based composite material obtained in Example 18;

[0026] Figure 6 XRD patterns of porous Al-Ce based composites before and after water treatment;

[0027] Figure 7 Comparison of the adsorption effects of different Ce-based precursors and commercial oxides on fluoride ions;

[0028] Figure 8 The effect of different pH values ​​on the adsorption of arsenic;

[0029] Fig. 9 The effect of different pH values ​​on the adsorption of fluorine;

[0030] Fig.10 is the adsorption efficiency of arsenic at different adsorption times;

[0031] Fig.11 is the adsorption efficiency of fluorine at different adsorption times;

[0032] Fig.12 is the adsorption capacity of porous Al-Ce based composite materials for arsenic and fluorine at different initial concentrations;

[0033] Fig.13 Arsenic concentration before and after adsorption when treating geothermal and hot spring water with porous Al-Ce based composite materials;

[0034] Fig.14 Fluoride concentration before and after adsorption when porous Al-Ce based composite materials were used to treat geothermal water and hot spring water. DETAILED DESCRIPTION

[0035] The present invention provides a porous Al-Ce-based composite material, comprising aluminum-cerium oxide and aluminum-cerium sulfate; the aluminum-cerium oxide comprises aluminum oxide and cerium oxide; the aluminum-cerium sulfate comprises CeOSO4 and Al2(SO4)3.

[0036] In the present invention, the average BJH pore size distribution of the porous Al-Ce-based composite material is 24.01-30.18 nm, and in the embodiment of the present invention, it can be 25 nm, 28 nm or 30 nm; the specific surface area of ​​the porous Al-Ce-based composite material is preferably 2.45-22.41 m 2 / g, in the embodiment of the present invention, specifically can be 3m 2 / g, 5m 2 / g, 8m 2 / g, 10m 2 / g, 15m 2 / g, 18m 2 / g, 20m 2 / g or 22m 2 / g; the pore volume of the porous Al-Ce-based composite material is preferably 0.001 to 0.052 cm 3 / g, in the embodiment of the present invention, specifically can be 0.008cm 3 / g, 0.01cm 3 / g, 0.03cm 3 / g or 0.05cm 3 / g.

[0037] In the present invention, the particle size of the porous Al-Ce-based composite material is preferably 200 nm. In the present invention, the porous Al-Ce-based composite material has a mesoporous structure. The present invention preferably agglomerates and composites together in the form of nanoparticles to form the porous Al-Ce-based composite material.

[0038] The porous Al-Ce-based composite material provided by the present invention can be hydrolyzed to form hydroxyl groups when used as an adsorbent for water treatment, and can exchange and adsorb fluoride ions and arsenic ions, thereby effectively removing fluoride ions (F - ) and arsenic ions (mainly HAsO4 2- exist).

[0039] In addition, since the Al-Ce composite material provided by the present invention has a porous structure, the exposure of the bifunctional groups (i.e., hydroxyl and sulfate groups, which are not completely converted into cerium oxide and aluminum oxide after calcination, and sulfate groups still remain in the composite) is increased, thereby increasing the active adsorption sites of the adsorbent, which is conducive to the contact between the target pollutants in the aqueous solution and the adsorbent, thereby achieving the removal of fluorine and arsenic ions in the water. The results of the embodiment show that the adsorption rate of the porous Al-Ce-based composite material provided by the present invention for fluorine ions is 91.47%, the adsorption rate for arsenic ions is 93.8%, and the adsorption capacity for fluorine ions and arsenic ions is 297 mg / g and 251 mg / g, respectively.

[0040] The present invention provides a method for preparing the porous Al-Ce based composite material described in the above scheme, comprising the following steps:

[0041] A mixture of a soluble cerium salt and a soluble aluminum salt is calcined in an oxygen-containing atmosphere to obtain the porous Al-Ce-based composite material; the soluble cerium salt includes Ce(SO4)2·4H2O and / or Ce(SO4)2·2(NH4)SO4; the soluble aluminum salt includes Al2(SO4)3·18H2O.

[0042] Unless otherwise specified, the materials and equipment used in the present invention are commercially available products.

[0043] In the present invention, the preparation of the mixture of soluble cerium salt and soluble aluminum salt preferably comprises: mixing soluble cerium salt, soluble aluminum salt and water, heating to evaporate the water, and obtaining the mixture of soluble cerium salt and soluble aluminum salt.

[0044] In the present invention, the mass ratio of aluminum in the soluble aluminum salt to cerium in the soluble cerium salt is preferably (0-10): (0-10), and both are not 0. In embodiments of the present invention, it can be 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2:8 or 1:9. In the present invention, the heating temperature is preferably 60-90°C. In embodiments of the present invention, it can be 60°C, 70°C, 80°C, 85°C or 90°C.

[0045] In the present invention, the system can be made homogeneous by adopting the preparation method of the mixture of the above-mentioned soluble cerium salt and soluble aluminum salt. The present invention does not limit the amount of water used, as long as the system can be made homogeneous. Since too much water evaporates for too long, and too little water does not dissolve well, in an embodiment of the present invention, the total mass of the soluble cerium salt and the soluble aluminum salt and the volume ratio of water are preferably 1g:10mL.

[0046] The present invention has no special requirement for the heating time, as long as the water can be evaporated. In the present invention, the heating is preferably carried out in a water bath; and the heating is preferably carried out under stirring.

[0047] After obtaining the mixture of the soluble cerium salt and the soluble aluminum salt, the present invention calcines the mixture of the soluble cerium salt and the soluble aluminum salt in an oxygen-containing atmosphere to obtain the porous Al-Ce-based composite material.

[0048] In the present invention, the calcination temperature is preferably 400-700°C, and in the embodiments of the present invention, it can be 400°C, 500°C, 600°C and 700°C; the calcination time is preferably 1-5h, and in the embodiments of the present invention, it can be 1h, 2h, 3h, 4h or 5h; the calcination atmosphere is preferably air. The present invention preferably heats from room temperature to the calcination temperature, and the heating rate is preferably 5°C / min. The present invention controls the calcination temperature at 400-700°C, which will cause a portion of sulfate to remain in the composite material, existing in the porous Al-Ce-based composite material in the form of CeOSO4 and Al2(SO4)3.

[0049] In the calcination process of the present invention, Al ions and Ce ions in the mixture of the soluble cerium salt and the soluble aluminum salt form a composite material containing Al2O3, CeO2, CeOSO4 and Al2(SO4)3.

[0050] After the calcination, the present invention preferably grinds the obtained composite material. The present invention has no special requirements for the particle size of the grind, and a particle size well known in the art can be used. The present invention grinds the obtained composite material for easy storage and does not affect the adsorption effect during application.

[0051] In the present invention, part of the sulfate radical generates water, sulfur dioxide and oxygen during the calcination process. Due to the loss of these gases, pores are formed, which play the role of pore-forming agent, thereby forming a porous Al-Ce-based composite material, and the other part is retained in the composite material. This porous Al-Ce-based composite material can be hydrolyzed to form hydroxyl groups when used as an adsorbent for water treatment. The sulfate radical retained in the composite material and the hydroxyl groups formed by hydrolysis are ion-exchanged and adsorbed with fluoride ions and arsenic ions, thereby effectively removing fluoride ions and arsenic ions in water.

[0052] The present invention provides the use of the porous Al-Ce-based composite material described in the above scheme as an adsorbent in water treatment.

[0053] In the present invention, the concentration of the porous Al-Ce-based composite material in the water to be treated is preferably 0.2-1 g / L. In an embodiment of the present invention, it can be 0.2 g / L, 0.4 g / L, 0.6 g / L, 0.8 g / L or 1 g / L. The fluoride ion concentration in the water to be treated is preferably ≤17.55 mg / L, and the arsenic ion concentration is preferably ≤2.39 mg / L.

[0054] In the present invention, the method of application preferably comprises the following steps:

[0055] The porous Al-Ce-based composite material and the water to be treated are mixed for adsorption. In the present invention, the water to be treated preferably includes geothermal water or hot spring water. In the present invention, the adsorption temperature is preferably 30 to 90°C, and in the embodiment of the present invention, it can be 30°C, 40°C, 50°C, 60°C, 70°C, 80°C or 90°C; the adsorption time is preferably 0.5 to 4h, and in the embodiment of the present invention, it can be 0.5h, 1h, 2h, 3h or 4h; the pH value of the water to be treated is preferably 6 to 9, and more preferably 8 to 9.

[0056] In the present invention, the optimal pH range for removing As and F is 8 to 9. Considering that the actual pH range of geothermal water is between 7.5 and 9.5, in actual geothermal water removal, the water sample does not need to adjust the pH, and the tedious operation of adjusting the pH can be avoided.

[0057] Figure 1 The figure is a schematic diagram of the preparation of the porous Al-Ce-based composite material of the adsorbent of the present invention and the process of removing fluorine and arsenic from geothermal water. Figure 1 As shown in the figure, a porous Al-Ce-based composite material was prepared by a one-step method of "solvent evaporation-high temperature pyrolysis". First, the metal precursors aluminum sulfate 18hydrate and cerium sulfate were dissolved and dried in an oven at 80°C. Then, the dried sample was calcined in a muffle furnace at 600°C for 4 hours. The sulfate group acted as a pore-forming agent during the calcination process, which was conducive to the formation of a porous structure, thereby exhibiting excellent removal performance. In aqueous solution, after the adsorbent was hydrolyzed at high temperature, M-OH groups (i.e., aluminum hydroxide and cerium hydroxide) appeared. Through the M-OH hydroxyl functional group and the sulfate group retained in the composite material, it reacted with the target ion As (in the form of HAsO4 2- Existence) and F - Ion exchange occurs, resulting in efficient removal.

[0058] In order to further illustrate the present invention, a porous Al-Ce-based composite material provided by the present invention and its preparation method and application are described in detail below in combination with the accompanying drawings and embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0059] Examples 1 to 9

[0060] Cerium sulfate tetrahydrate (Ce(SO4)2·4H2O) and aluminum sulfate 18hydrate (Al2(SO4)3·18H2O) are added into 10 mL of water, wherein the total mass of cerium sulfate tetrahydrate and aluminum sulfate 18hydrate is 1 g, and the mass ratio of Al / Ce is maintained at 9 / 1, 8 / 2, 7 / 3, 6 / 4, 5 / 5, 4 / 6, 3 / 7, 2 / 8 and 1 / 9 respectively. The mixture is stirred and volatilized in a water bath at 80°C, and then transferred to a muffle furnace for calcination at a temperature of 600°C for 4 hours. The temperature is raised from room temperature at a rate of 5°C / min to obtain a porous Al-Ce-based composite material.

[0061] Comparative Examples 1-2

[0062] The preparation steps are the same as those in Example 1, except that the mass ratio of Al / Ce is kept at 10 / 0 or 0 / 10 respectively.

[0063] Embodiments 10 to 13

[0064] Cerium sulfate tetrahydrate and aluminum sulfate 18hydrate are added to 10 mL of water, the total mass of cerium sulfate tetrahydrate and aluminum sulfate 18hydrate is 1 g, the mass ratio of Al / Ce is maintained at 2 / 8, and the mixture is stirred and volatilized in a water bath at 80°C, and then transferred to a muffle furnace for calcination at 400, 500, 600 and 700°C for 4 hours. The temperature is raised from room temperature at a rate of 5°C / min to obtain a porous Al-Ce based composite material.

[0065] Embodiments 14 to 17

[0066] Ammonium cerium sulfate Ce(SO4)2·2(NH4)SO4 and aluminum sulfate 18hydrate are added to 10 mL of water, wherein the total mass of the ammonium cerium sulfate and aluminum sulfate 18hydrate is 1 g, and the mass ratio of Al / Ce is maintained at 2 / 8. The mixture is stirred and volatilized in a water bath at 80°C, and then transferred to a muffle furnace for calcination at 400, 500, 600 and 700°C for 4 hours. The temperature is raised from room temperature at a rate of 5°C / min to obtain a porous Al-Ce based composite material.

[0067] Comparative Examples 3 to 6

[0068] Cerium chloride and aluminum sulfate 18hydrate were added to 10 mL of water. The total mass of cerium chloride and aluminum sulfate 18hydrate was 1 g. The mass ratio of Al / Ce was maintained at 2 / 8. The mixture was stirred and volatilized in a water bath at 80°C. The mixture was then transferred to a muffle furnace and calcined at 400, 500, 600 and 700°C for 4 hours. The temperature was raised from room temperature at a rate of 5°C / min to obtain a porous Al-Ce-based composite material.

[0069] Comparative Examples 7 to 10

[0070] Cerium acetate and aluminum sulfate 18hydrate are added to 10 mL of water. The total mass of cerium acetate and aluminum sulfate 18hydrate is 1 g. The mass ratio of Al / Ce is maintained at 2 / 8. The mixture is stirred and volatilized in a water bath at 80°C. The mixture is then transferred to a muffle furnace and calcined at 400, 500, 600 and 700°C for 4 hours. The temperature is raised from room temperature at a rate of 5°C / min to obtain a porous Al-Ce-based composite material.

[0071] Embodiment 18

[0072] Cerium sulfate tetrahydrate and aluminum sulfate 18hydrate are added to 10 mL of water. The total mass of cerium sulfate tetrahydrate and aluminum sulfate 18hydrate is 1 g. The mass ratio of Al / Ce is maintained at 2 / 8. The mixture is stirred and volatilized in a water bath at 80°C. The mixture is then transferred to a muffle furnace and calcined at 600°C for 4 hours. The temperature is raised from room temperature at a rate of 5°C / min to obtain a porous Al-Ce-based composite material.

[0073] Figure 5 The transmission electron microscope micrograph of the porous Al-Ce-based composite material obtained in Example 18 is shown in FIG. Figure 5 It can be seen that the particle size of the porous Al-Ce-based composite material is about 200nm, and the two oxide particles in the material are evenly distributed. The pore structure was characterized by Brunner-Emmet-Teller (BET) and tested by Quadrasorb SI in the United States. The results showed that the average BJH pore size distribution was 28.8444nm and the specific surface area was 7.1549m 2 / g, pore volume is 0.051595cm 3 / g.

[0074] Embodiment 19

[0075] The preparation method is the same as that of Example 18, except that cerium sulfate tetrahydrate is replaced by ammonium cerium sulfate Ce(SO4)2·2(NH4)SO4.

[0076] Comparative Examples 11 to 13

[0077] The preparation method is the same as that of Example 18, except that cerium sulfate tetrahydrate is replaced by commercial CeO2, cerium acetate Ce(CH3COO)2 and cerium chloride CeCl3.

[0078] Application Example 1

[0079] Take 30 mg of the porous Al-Ce-based composite material obtained in Examples 1 to 9 and Comparative Examples 1 to 2, add it to 30 mL of a solution containing arsenic ions and fluoride ions at a pH of 8.82, the initial concentration of arsenic ions is 2.39 mg / L, the initial concentration of fluoride ions is 17.55 mg / L, the solid-liquid ratio of the solution to the porous Al-Ce-based composite material is 1 g / L, and keep it in a constant temperature water bath shaker at 80°C for 4 hours at 180 r / min. After filtering, take the solution and use an ion selective electrode to determine the residual fluoride ion concentration. Use an inductively coupled plasma mass spectrometer (ICP-MS, PerkinElmer, NexION1000, USA) to determine the residual arsenic ion concentration, and calculate its adsorption efficiency. The results are shown in Figure 2 and Figure 3 .

[0080] Depend on Figures 2-3 It can be seen that as the Al / Ce mass ratio increases from 10 / 0 to 2 / 8, the adsorption performance of the material becomes better. When the Al / Ce mass ratio is 2 / 8, the residual concentration of arsenic in the solution is less than 50 ng / mL, and the residual concentration of fluorine is less than 1 mg / L.

[0081] Application Example 2

[0082] The porous Al-Ce-based composite materials and commercial cerium oxide (directly used as an adsorbent) of Examples 10 to 17 and Comparative Examples 3 to 10 at different calcination temperatures were respectively taken, and the adsorption efficiency of the composite materials on fluoride ions was tested according to the test method of Application Example 1, that is, only a solution containing fluoride ions was prepared and tested according to the method of Application Example 1. The results are shown in Figure 4 .

[0083] Depend on Figure 4 It can be seen that the effect of cerium precursors on adsorbing F ions is as follows: cerium sulfate > ammonium cerium sulfate > cerium chloride > commercial cerium oxide > cerium acetate. The Ce oxides generated by calcining cerium sulfate and ammonium cerium sulfate as precursors have significantly better adsorption of fluoride ions than other cerium precursors. As the temperature increases, there is no difference in the performance of the materials, indicating that the temperature has little effect on the calcination. The calcination temperature of 400-700℃ has no significant effect on the adsorption efficiency of fluoride ions of the four Ce oxides.

[0084] Application Example 3

[0085] Figure 7The adsorption effect of different Ce-based precursors and commercial oxides on fluoride ions is compared. 30 mg of the porous Al-Ce-based composite material prepared in Example 18 was added to 30 mL of a solution containing only fluoride ions at a pH of 8.82. The initial concentration of fluoride ions was 17.55 mg / L, and the solid-liquid ratio of the fluoride ion solution to the porous Al-Ce-based composite material was 1 g / L. The mixture was kept in a constant temperature water bath shaker at 180 r / min for 3 hours at 80°C. After filtration, the solution was taken and the residual fluoride ion concentration was determined using an ion selective electrode, and its adsorption efficiency was calculated. In order to evaluate the removal performance of the prepared materials, under the same conditions, the performance of commercial CeO2 (directly used as an adsorbent) and cerium-based precursors tetrahydrate cerium sulfate Ce(SO4)2·4H2O, ammonium cerium sulfate Ce(SO4)2·2(NH4)SO4, cerium acetate Ce(CH3COO)2 and cerium chloride CeCl3 (i.e., the materials obtained in Example 19 and Comparative Examples 11 to 13) were compared. The results are shown in Table 1. Figure 7 .

[0086] Depend on Figure 7 It can be seen that the CeO2 prepared by the present invention using Ce(SO4)2·4H2O and Ce(SO4)2·2(NH4)SO4 as precursors has an adsorption efficiency of fluorine of 98.18% and 96.87% respectively, which is much higher than other cerium compounds Ce(CH3COO)2 and CeCl3; while the adsorption efficiency of commercialized CeO2 for fluorine is only 11.54%, and the residual fluorine concentration after adsorption cannot meet the limit standard of fluorine in surface water. Figure 7 As shown in the small figure in the upper right corner, after Ce(SO4)2·4H2O and Ce(SO4)2·2(NH4)SO4 of the present invention adsorb fluoride ion solution as adsorbents, the concentrations of remaining fluoride ions in the solution are 0.32 mg / L and 0.55 mg / L respectively. Therefore, the soluble cerium salts prepared by the present invention are preferably Ce(SO4)2·4H2O and Ce(SO4)2·2(NH4)SO4.

[0087] Application Example 4

[0088] When the initial concentrations of fluorine and arsenic were 17.55 mg / L and 2.39 mg / L, respectively, and the solid-liquid ratio was 1 g / L, the adsorption performance of the porous Al-Ce-based composite material obtained in Example 18 for fluorine ions and arsenic ions in the pH range of 2 to 13 was 4 h, and the other conditions were the same as those in Application Example 1. Figures 8-9 .

[0089] Depend on Figures 8-9It can be seen that within the range of 7 to 9, the material's adsorption efficiency for arsenic and fluoride is nearly 100%. When the pH rises to 10, the concentration of remaining arsenic in the solution is higher than 50 ng / mL. This shows that the material's adsorption of arsenic and fluoride is adapted to the weakly alkaline geothermal water environment. Due to the deprotonation of the material surface under alkaline conditions, it is not suitable for the adsorption of negatively charged arsenic and fluoride ions. When the pH is between 7 and 9, the concentrations of arsenic and fluoride ions in the adsorbed solution meet the limit values ​​of arsenic (less than 50 ng / mL) and fluoride (less than 1 mg / L) in the Class I surface water quality standards stipulated by my country.

[0090] In addition, the isoelectric pH of the porous Al-Ce-based composite material prepared by the present invention is zpc The optimal pH range for the adsorption of arsenic and fluorine in geothermal water is 7 to 9, and the actual pH range for geothermal water is 8 to 9. Therefore, in practical applications, the pH of water samples does not need to be adjusted, and the tedious operation of adjusting the pH can be avoided.

[0091] Application Example 5

[0092] When the initial concentrations of fluorine and arsenic were 17.55 mg / L and 2.39 mg / L respectively, the solid-liquid ratio was 1 g / L, and the effect of adsorption equilibrium time on the porous Al-Ce-based composite material at pH 8.82 was investigated. Other conditions were the same as those in Application Example 1. The results are shown in Figures 10-11 , the black curves represent the residual ion concentrations of fluorine and arsenic.

[0093] Depend on Figures 10-11 It can be seen that the material exhibits relatively fast adsorption kinetics for As(V) and F. It exhibits extremely fast kinetics for arsenic ions, achieving an adsorption efficiency of 93.8% within 10 minutes, and after 50 minutes of reaction, the concentration of As is lower than the Class I water quality limit standard for surface water. For fluorine, an adsorption efficiency of 91.47% can be achieved within 15 minutes, and after 50 minutes, the concentration of F ions is lower than the Class I water quality limit standard for surface water. Most of the Al2O3 equilibrium times reported in the literature are as long as 1440 minutes. It can be seen that the composite material prepared by the present invention has relatively fast kinetics for As ions and F ions, and has broad prospects in practical applications.

[0094] Application Example 6

[0095] Fig.12 is the adsorption capacity of porous Al-Ce based composite materials for arsenic and fluorine at different initial concentrations. Adsorption capacity is an important indicator for evaluating adsorbent performance and adsorption efficiency.

[0096] The test method is a static adsorption method: dilute 1000 mg / L As standard solution to As concentration gradients of 5, 10, 20, 40, 60, 80, 100, 200, 300, 400, and 500 mg / L, add 30 mg of adsorbent to 30 mL of the solution corresponding to the As concentration gradient, and other conditions are the same as in Application Example 1. The residual As concentration is measured by ICP-MS to calculate the adsorption capacity.

[0097] Dilute 1000 mg / L F standard solution to initial F concentrations of 5, 10, 20, 40, 60, 80, 100, 200, 300, 400, 500, 600, and 700 mg / L, and add 30 mg to 30 ml of the solution corresponding to the F concentration gradient. Other conditions are the same as those in Application Example 1. Measure the remaining F concentration with a fluorine electrode to calculate the adsorption capacity.

[0098] like Fig.12 As shown, the adsorption capacity of the Al / Ce composite material obtained in Example 18 as an adsorbent for F ions and As ions is 297 mg / g and 251 mg / g, respectively, which is much higher than the previously reported metal oxide adsorption, and is particularly suitable for the removal of high-concentration wastewater containing As ions and F ions.

[0099] Application Example 7

[0100] The removal effect of the porous Al-Ce-based composite material (Al / Ce mass ratio 2:8) prepared in Example 18 on actual geothermal water was investigated. Actual geothermal water and hot spring water were collected from Yangbajing, Tibet, with a pH value of 8.82. The initial concentrations of F ions and As ions in the actual geothermal water were as high as 17.55 and 2.39 mg / L, respectively. The initial concentrations of F ions and As ions in the actual hot spring water were as high as 30.6 and 5.1 mg / L, respectively. After 30 mg of the prepared porous Al-Ce-based composite material (adsorbent) was added to 30 mL of the actual water sample, the other conditions were the same as those in Application Example 1. The concentrations of fluorine and arsenic before and after adsorption were as follows: Figures 13-14 shown.

[0101] Depend on Figures 13-14 It can be seen that the Al-Ce composite material prepared by the present invention can achieve an adsorption efficiency of up to 96.4% and 98.7% for F ions and As ions in geothermal water, and the remaining concentrations after adsorbing F ions and As ions are 0.63 mg / L and 31.07 ng / mL, respectively. The material can achieve an adsorption efficiency of up to 98.4% and 99.8% for F ions and As ions in hot spring water, and the remaining concentrations after adsorbing F ions and As ions are 0.49 mg / L and 10.2 ng / mL, respectively.

[0102] In order to study the crystal structure of the material and the hydrolysis mechanism of the porous Al-Ce-based composite material in the solution, the materials prepared in Example 18 and Comparative Examples 1 to 2 were characterized by XRD. Figure 6 , the lines from top to bottom are the oxide after single calcination of Al2(SO4)3·18H2O (i.e. the material obtained in comparative example 1), the oxide after single calcination of Ce(SO4)2·4H2O (i.e. the material obtained in comparative example 2), the material after As adsorption by the Al-Ce based composite material of Example 18 (the method is the same as that of Application Example 6, and the concentration of arsenic ions is 100 mg / L), the material after F adsorption by the Al-Ce based composite material of Example 18 (the method is the same as that of Application Example 6, and the concentration of fluoride ions is 100 mg / L), the material after hydrolysis of the Al-Ce based composite material of Example 18 in aqueous solution (without adding target ions arsenic and fluorine, the method is the same as that of Application Example 6), the Al-Ce based composite material of Example 18, the Al2(SO4)3 standard substance card and the CeOSO4 standard substance card.

[0103] Depend on Figure 6 It can be seen that the prepared porous Al-Ce-based composite material has the same peak position as Al2(SO4)3 standard PDF card (PDF#30-0043), CeOSO4 standard PDF card (PDF#39-0515), Al2O3 standard PDF card (PDS#52-0803) and CeO2 standard PDF card (PDF#44-1001), indicating that the porous Al-Ce-based composite material of the present invention is composed of aluminum oxide, cerium oxide, CeOSO4 and Al2(SO4)3; and the XRD peak is very messy, indicating that the composition of the composite is relatively complex. After the Al-Ce composite material is hydrolyzed, new peaks appear at 1 and 3, corresponding to the peaks of 2θ at 16.1° and 28.2° in Ce2(SO4)3 standard PDF card (PDF#01-0208) and Ce(OH)3 standard PDF card (PDF#19-0284), respectively. In addition, the peaks a, c, e, g, i, j, l, m, and n of the Al-Ce composite material disappeared, and the h peak weakened to 2 peaks, indicating that CeO2 was severely hydrolyzed to generate Ce(OH)3 in aqueous solution. New peaks appeared at 4 and 5 (2θ at 40.8° and 43.7°) after hydrolysis of the Al-Ce composite material, corresponding to the (303) and (222) crystal planes in the Al2(SO4)3 standard PDF card (PDF#30-0043) and Al(OH)3 standard PDF card (PDF#26-0025), respectively. In addition, the peaks b, d, and f of the Al-Ce composite material disappeared, and the k peak weakened, indicating that Al2O3 was severely hydrolyzed to generate Al(OH)3 in aqueous solution. After adsorbing F ions and As ions, the hydroxyl peak weakened slightly, and new peaks appeared, indicating that F ions and As ions were successfully adsorbed.

[0104] my country stipulates that the arsenic content in the Class I surface water quality index is less than 50ng / mL, and the fluorine content is less than 1mg / L. Therefore, the concentrations of fluorine and arsenic remaining in the geothermal water after being treated with the porous Al-Ce-based composite material of the present invention meet the limits of F and As in my country's surface water environmental quality standards.

[0105] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A porous Al-Ce-based composite material, comprising aluminum-cerium oxide and aluminum-cerium sulfate; the aluminum-cerium oxide comprises aluminum oxide and cerium oxide; the aluminum-cerium sulfate comprises CeOSO4 and Al2(SO4)3; the BJH pore size distribution average value of the porous Al-Ce-based composite material is 24.01 to 30.18 nm.

2. The porous Al-Ce based composite material according to claim 1, characterized in that: The specific surface area of ​​the porous Al-Ce-based composite material is 2.45 to 22.41 m 2 / g, pore volume is 0.001~0.052cm 3 / g, particle size is 200nm.

3. The method for preparing the porous Al-Ce based composite material according to claim 1 or 2, comprising the following steps: A mixture of a soluble cerium salt and a soluble aluminum salt is calcined in an oxygen-containing atmosphere to obtain the porous Al-Ce-based composite material; the soluble cerium salt includes Ce(SO4)2·4H2O and / or Ce(SO4)2·2(NH4)SO4; the soluble aluminum salt includes Al2(SO4)3·18H2O.

4. The preparation method according to claim 3, characterized in that: The calcination temperature is 400-700° C. and the calcination time is 1-5 hours.

5. The preparation method according to claim 3 or 4, characterized in that: The mass ratio of aluminum in the soluble aluminum salt to cerium in the soluble cerium salt is (0-10):(0-10), and both are not 0.

6. The preparation method according to claim 3 or 4, characterized in that: The calcination atmosphere is air.

7. The preparation method according to claim 3, characterized in that: The preparation of the mixture of soluble cerium salt and soluble aluminum salt comprises: mixing soluble cerium salt, soluble aluminum salt and water, heating to evaporate the water, and obtaining the mixture of soluble cerium salt and soluble aluminum salt.

8. The preparation method according to claim 7, characterized in that: The heating temperature is 60-90°C.

9. Use of the porous Al-Ce based composite material according to claim 1 or 2 or the porous Al-Ce based composite material prepared by the preparation method according to any one of claims 3 to 8 as an adsorbent in water treatment.

10. The use according to claim 9, characterized in that: The concentration of the porous Al-Ce-based composite material in the water to be treated is 0.2-1 g / L; the fluoride ion concentration in the water to be treated is ≤17.55 mg / L, and the arsenic ion concentration is ≤2.39 mg / L.